Adverse childhood experiences, paraphilias, and serious criminal violence among federal sex offenders. Issue 2 (2nd May 2017) - Drury, Alan; Heinrichs, Tim; Elbert, Michael; Tahja, Katherine; DeLisi, Matt; Caropreso, Daniel
Abstract : Purpose: Adverse childhood experiences (ACEs) are a broad conceptual framework in the social sciences that have only recently been studied within criminology. The purpose of this paper is to utilize this framework by applying it to one of the most potentially dangerous forensic populations. Design/methodology/approach: Archival data from 225 federal sex offenders was used to perform descriptive, correlational, and negative binomial regression models. Findings: There was substantial evidence of ACEs including father abandonment/neglect (36 percent), physical abuse (nearly 28 percent), verbal/emotional abuse (more than 24 percent), and sexual abuse (approximately 27 percent). The mean age of sexual victimization was 7.6 years with the youngest age of victimization occurring at the age of 3. Offenders averaged nearly five paraphilias, the most common were pedophilia (57 percent), pornography addiction (43 percent), paraphilia not otherwise specified (35 percent), exhibitionism (26 percent), and voyeurism (21 percent). The offenders averaged 4.7 paraphilias and the range was substantial (0 to 19). Negative binomial regression models indicated that sexual sadism was positively and pornography addiction was negatively associated with serious criminal violence. Offenders with early age of arrest onset and more total arrest charges were more likely to perpetrate kidnaping, rape, and murder. Originality/value: ACEs are common in the life history of federal sex offenders, but have differential associations with the most serious forms of crime.